Effects Of Human Activities on Wetland: Perspectives from King’Wal Wetland in Nandi County, Kenya - Kipsang, Margaret Jepkemoi (JOOUST, 2024)
Wetlands across the world offer a variety of essential ecosystem services that are essential to people and biodiversity's continued existence, health, and wellbeing. Despite the benefits provided by wetlands, they continue being encroached through human activities, hence there is need to put in place mechanisms to conserve them. The study main objective was to investigate the effects of human activities on wetland vegetation: Perspective of King’wal in Nandi County, Kenya. Specifically, the study sought to establish how brick making causes wetland de- vegetation, to examine the effects of farming on the biomes of King’wal wetland in Nandi County and to assess the level of awareness of the community on the importance of wetlands in relation to their encroachment activities. The study adopted Ecological theory. The study used descriptive survey research design. The study utilized questionnaires and interview schedule as the main data collection tools. The target population was 1325 household units. The sample size of the study was 126 brick makers and farmers. Purposive sampling technique was used to select brick makers and farmers while census sampling method was used to choose 10 key informants charged with the responsibilities of dealing with environmental matters. Quantitative data collected was analyzed using both descriptive statistics (frequencies, percentages and means) and inferential statistics (Pearson’s moment of correlation) using SPSS and Microsoft excel, while the qualitative data was analyzed thematically. The data was presented in form of tables, frequencies, percentages and graphs. The study results established that there was a weak positive correlation between brick making and wetland de-vegetation, which was statistically significant (r=.218, n=126, P= .014). The study found that wetland degradation has occurred due to extensive farming on wetland vegetation by use of agrochemical and excessive leaching of nutrients. The study findings also revealed that there was a strong positive correlation between farming on biomes and wetland de-vegetation, which was statistically significant (r=.724, n=126, P= .000). There was a weak negative correlation between level of awareness and wetland de- vegetation, which was statistically significant (r=-.299, n=126, P= .001). The following conservation measures were mentioned by the respondents; enacting of legislation to curb use of wetland, controlling brick making, planting indigenous trees, conducting frequent barazas and enforcement of laws on wetland encroachment, stationing NEMA, KWS and County Government surveillance. The study concludes that extensive brick making poses a danger to wetland biomes going into extinction unless measures are taken to preserve the wetland. The continued expansion of both small and large scale farming areas has threatened the presence and existence of the ecosystem. Some of the largest impacts are through drainage and conversion of Kingwal wetland into cultivated land; that has drastically reduced the land under wetland. The locals were well aware of the value of wetlands. Rarely were community gatherings held with locals organized when they should have been instructed on how to prevent endangering Kingwal Wetland and the need of protecting it. The study suggests that, in order to protect Kingwal Wetland from unwarranted threats and promote its sustainability future generations, the County Government of Nandi and the Federal Government should create and strictly enforce policies governing human activities carried out within or close to the Kingwal Wetland.
Keywords: Human Activities; Wetland; King’Wal Wetland